Erratum - Analysis of extracellular superoxide dismutase and Akt in ascending aortic aneurysm with tricuspid or bicuspid aortic valve - A. Arcucci (European Journal of Histochemistry, 2015)
This correct the article published on European Journal of Histochemistry 2014;58:200-206 doi: 10.4081/ejh.2014.2383